A Photocaged Azidosugar for Light‐Controlled Metabolic Labeling of Cell‐Surface Sialoglycans. Issue 7 (22nd January 2022) - Cheng, Bo; Wan, Yi; Tang, Qi; Du, Yifei; Xu, Feiyang; Huang, Zhimin; Qin, Wei; Chen, Xing
Comprehensive Summary: The photocaging strategy has been widely used for activating biomolecules and hence regulating the underlying biological processes with high temporal and spatial resolution. Herein, we integrate this strategy into metabolic glycan labeling, which enables optically‐controlled metabolic labeling of cell‐surface sialoglycans with azides. N ‐Azidoacetylmannosamine (ManNAz) is caged with a 4, 5‐dimethoxy‐2‐nitrobenzyl (DMNB) group at the anomeric hydroxyl group to block its cellular metabolism. After feeding to the cells, irradiation with 365 nm UV light or 405 nm visible light cleaves the photocage and generates ManNAz within the cells. ManNAz is metabolically converted to azido sialic acid, which is then incorporated into cell‐surface sialoglycans. We demonstrated spatial and temporal control of this strategy by specifically labeling sialoglycans on a single cell and tracking the metabolism of ManNAz based on light‐triggered pulse‐chase labeling, respectively. The light‐controlled metabolic glycan labeling strategy should facilitate probing of glycosylation in complex biological systems with high spatiotemporal precision. Abstract : Unnatural sugars with bioorthogonal chemical reporters can be chemically conjugated with a photolabile caging group to block the cellular metabolism. The photocage can be cleaved by 365 nm UV light or 405 nm visible light to release azidosugars to label cell‐surface sialoglycans. We demonstrated spatial and temporal control of this strategy by specifically labeling sialoglycans on a single cell and tracking the metabolism of ManNAz based on light‐triggered pulse‐chase labeling, respectively.